Stressors, Stress Reaction, Social Support and Satisfaction of Resident-in-training in Far Eastern University – Nicanor Reyes Medical Foundation Medical Center - Reyes, Juan Enrique J.; Maria, Michael Ian N. Sta.; Joves Jr, Policarpio B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Background: Residency training can render a wide variety of stressors that can affect the residents-in- training’s level of well-being and performance. Long hours of duty in the hospital together with physical and mental fatigue had become acceptable as these were believed to impart toughness to prepare physicians for a career in Medicine. This study was done to identify the stressors experienced by Far Eastern University – Nicanor Reyes Medical Foundation (FEU-NRMF) Medical Center residents-in- training using the Brief Job Stress Questionnaire. Likewise, the relationship between the stressors and the demographic profile of the resident was explored. Methods: This is a single-center descriptive cross-sectional study of all resident physicians of the FEU- NRMF Medical Center. The demographic data which includes age, sex, civil status, specialty training, and years in training were sought using a self-administered questionnaire. The stressors, stress reaction, social support, and job satisfaction of residents were identified using the Brief Job Stress Questionnaire (BSQ) which is a validated self-administered questionnaire used in Japan. Data were analyzed using descriptive statistics, presented in tables. The relationships between the stressors and demographic data were analyzed using chi-square and t-test. Results: The mean age of the residents-in-training who responded was 29-years old and the majority were females (71%) and single (85%). Mostly came from Internal Medicine training (23%) and were within the first three years of training (83%). The BSQ showed that the psychological stressors of resident-in-training were lack of meaningfulness of work (94%), skill under-utilization (90%), and unsuitable job (85%). In terms of stress reaction, mostly felt fatigued (65%), and anxious (32%). Residents-in-training social support came from their supervisors (86%) and co-workers (60%). Most of them were satisfied with their job (81%) and family life (78%). Among the different stressors, physical demand was the only variable significantly associated with sex (p-value, 0.015) and specialty (p-value, 0.004). Conclusion: The research was able to identify the different job stressors, stress reaction, social support, and satisfaction with job and family life of the residents-in-training in FEU-NRMF Medical Center. This will be a starting point in planning and creating programs that will help residents cope with the stress of residency training.